Returns on Investments of HIV Prevention in Vietnam - Zhang, Lei; Pham, Quang Duy; Do, Mai Hoa; Kerr, Cliff; Wilson, David P. (World Bank, Washington, DC, 2018)
This study aimed to estimate the cost-effectiveness and returns on investments of HIV prevention programs implemented during 2006-2010 and to identify the optimal allocation of resources across combinations of programs for an effective HIV prevention response to inform the prioritization of funding and health resources in Vietnam. The spending-outcome relationships and an epidemiological model were used to compare observed conditions with counterfactual scenarios of reduced or no programs to calculate the cost-effectiveness and estimate healthcare costs saved and thus the return on investment. Model simulations of epidemic projections over many combinations of possible resource allocations were used to identify optimal allocations for reducing new infections over the next HIV budget period.